Positive Correlation Between Women’s Status and Intimate Partner Violence Suggests Violence Backlash in Mwanza, Tanzania - Kilgallen, Joseph A. (Journal of interpersonal violence, 2022)
Urbanization in low and middle-income nations is characterized by economic and demographic shifts largely understood to be beneficial to women?s empowerment. These changes include increased education and wage-labor opportunities, a disruption of traditional patrilocal residence systems, and reductions in spousal age gap and fertility. However, such changes may drive a ?violence backlash,? with men increasing intimate partner violence (IPV) in efforts to challenge women?s shifting status. To date, tests of this idea primarily relate to women?s changing economic status, with less known about the demographic correlates of IPV in urbanizing settings. Addressing this, we conducted a cross-sectional study of IPV behavior and attitudes in an urbanizing community in Mwanza, northern Tanzania (n = 317). Consistent with a violence backlash, IPV was reported more often among women educated at higher levels than their husband, and women earning similar, rather than lower, wages to their husband were more likely to report that he condones IPV. These findings were independent of women?s absolute education and income. Furthermore, less frequent paternal kin contact, and relatively small spousal age gaps, generally understood to boost women?s empowerment, were associated with an increased risk of experiencing IPV. Less frequent paternal kin contact was also associated with an increased likelihood that a husband condones IPV. Contrary to our predictions, relatively lower fertility, generally linked to higher women?s empowerment, did not predict IPV behavior and women with high, rather than low, fertility were more likely to report that their husband condones IPV. Overall, our results support the notion of a violence backlash corresponding to economic changes for women that accompany urbanization. In contrast, demographic changes associated with urbanization have more variable relationships. Drawing on these results, we suggest future research avenues for better understanding the vulnerability of women to IPV in urbanizing settings.